Anti-inflammatory activity of the ethnolic extract of the leaves of manihot esculenta Crantz (yuca) in an experimental model of acute inflammation - Nathalie D. Amado-Cornejo; Geraldine Atusparia-Flores; Maricielo V. Huamán-Cabrera; Ángela Méndez-Pajares; Etty Prado-Asencios; Hilda Jurupe-Chico; Vilma Herencia-Reyes (Revista de la Facultad de Medicina Humana, 2020)
Introduction: Manihot esculenta Crantz (yucca) leaves have been used around the world and over time in order to decrease the anti-inflammatory response. Objective: To evaluate the anti-inflammatory activity of the ethanolic extract of the Manihot esculenta Crantz leaf in rats. Methods: An experimental study was conducted. The study population included 60 albino rats sp. Rattus novergicus, distributed in 4 groups of 15 rats each. A homogeneous solution of ethanolic extract of Manihot esculenta Crantz leaves was used for intraperitoneal administration. Carrageenan was used as an inflammatory inducer that was administered intradermally; for the measurement of plantar edema, the Digital Water Plethysmometer (LE7500) was used. Tween 80 / water solution (1:10) was administered to the negative control group at a dose of 1mL./100g., To the betamethasone positive control group 4mg / Kg and to treatment groups 1 and 2 Manihot esculenta Crantz, 2 mg / kg and 4 mg / kg, respectively. The 1-tail ANOVA test and the Tukey post hoc test were used for comparisons between the groups. Results: In 37.67% of treatment group 2 a reduction in edema was observed 3 hours after administering Manihot esculenta Crantz (p <0.05). In both administration groups of Manihot esculenta Crantz there was a nonsignificant trend to reduce plantar edema with values close to significance. Conclusion: The Manihot esculenta Crantz ethanolic extract at a 4 mg / kg dose probably have anti-inflammatory activity in this animal model of acute inflamation.